Second generation of the 1993 birth cohort, Pelotas (Brazil): Aims, design, preliminary results - Gonçalves, Helen (Health Sci Rep, 2020)
BACKGROUND AND AIMS: Longitudinal cohort studies examining different generations can explain how health problems can be transmitted through genetic and environmental mechanisms and their effects on the health of offspring. This study aimed to present the design and to describe the characteristics of the baseline sample of a second generation cohort. METHODS: The 93Cohort‐II is a dynamic prospective cohort composed of a second generation from the original 1993 Pelotas Birth Cohort (offspring), whose parents had their last follow‐up at 22 years old. Biological parents were asked to answer questions addressing the type of birth, general health status, family composition, dietary habits, breastfeeding habits, and child‐caregiver(s), among others, and the children's anthropometric measurements were evaluated. RESULTS: Of 1650 children identified, 1212 were evaluated (response rate, 73.4%), and 21 died before the baseline assessment. The age of the offspring ranged from 0 to 10 years (mean [±SD], 2.9 ± 2.1 years); most children (65.6%) lived with both parents and were born to young mothers and poor families. One‐third of the children were breastfed until 6 months of age, one‐half were born by cesarean section, 63.9% had used medication in the previous 15 days, 26.4% experienced hospitalization at least once since birth, and 14% had no updated vaccination; asthma/bronchitis (20.4%) and bronchiolitis (13.4%) were the most frequently reported diseases. More than 60% consumed ultra‐processed foods, and the prevalence of overweight among those <5 and ≥6 years of age was 10.2% and 18.9%, respectively. The mean total Child Behavior Checklist score was 44.1 ± 23.61 (≥16 months), and the mean intellectual quotient score in children ≥6 years of age was 97.9 ± 15.4. CONCLUSION: Despite the difficulties in conducting intergenerational cohort studies, the results of the present investigation provide evidence supporting the feasibility of performing these types of studies in middle‐income countries.